Integrated attitude determination and control system via magnetic measurements and actuation - Mohammad Abdelrahman, Mohammad Ibraheem; Park, Sang-Young (Pergamon, 2011)
A nonlinear control scheme using a Modified State-Dependent Riccati Equation (MSDRE) is developed through a pseudo-linearization of spacecraft augmented nonlinear dynamics and kinematics. The full-state knowledge required for the control loop is provided through a generalized algorithm for spacecraft three-axis attitude and rate estimation based on the utilization of magnetometer measurements and their time derivatives, while the control torque is generated via magnetorquers. The stability of the controller is investigated through Lyapunov function analysis and the local observability of the estimator is verified. The resulted attitude determination and control system has shown the capability of estimating the attitude better than 5 deg and rate of order 0.03 deg/s in addition to maintain the pointing accuracy within 5 deg in each axis with pointing stability of less than 0.05 deg/s. Monte-Carlo simulations are used to demonstrate the global asymptotic stability of the controller and the estimator for various initial conditions.